Creatine supplementation during a training camp in young professional cyclists: a randomized controlled trial - Revuelta, C.; Valenzuela, P. L.; Alejo, L. B.; Górriz, M.; Pagola, I.; Ozcoidi, L. M.; Lucía, A.; Barranco-Gil, D. (Journal of Science and Cycling, 2023)
Background: Growing evidence suggests that creatine supplementation can provide beneficial effects on exercise performance and recovery, particularly in strength/power sports. However, its effects on endurance athletes remain unclear. We aimed to assess the effects of short term creatine supplementation in professional cyclists during a training camp.